(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
This article deals with that stylistics, as a branch of linguistics, offers a unique lens through which to analyze language and communication. By focusing on the ways in which language is used to convey meaning, stylistics delves into the intricacies of linguistic choices, such as word selection, sentence structure, and tone. This article explores how these choices contribute to the overall style and effectiveness of a text, shedding light on the nuances of language that can shape our understanding and interpretation of written and spoken communication. In this article, we will delve into the fascinating world of stylistics and explore its relevance in understanding language and communication.